2008
DOI: 10.1055/s-2007-995748
|View full text |Cite
|
Sign up to set email alerts
|

Transoral gastroplasty is safe, feasible, and induces significant weight loss in morbidly obese patients: results of the second human pilot study

Abstract: This second pilot trial confirmed the feasibility and safety of transoral gastroplasty. The early results and technical improvements reported in the present study are encouraging in terms of safety, early weight loss, and quality of life, and clearly allowed multicenter trials, which are planned to start soon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 15 publications
0
56
0
2
Order By: Relevance
“…Deviere and Moreno have published pilot human studies using a transoral device to create a vertical gastroplasty. 10,11 The device named transoral gastroplasty (Satiety, Palo Alto, CA) contains a stapler body with two jaws and a septum with retraction wire to orient the stomach tissue for capture and stapling. Suction pulls tissue from the anterior and posterior walls of the stomach into the device and the stapler is closed and fired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deviere and Moreno have published pilot human studies using a transoral device to create a vertical gastroplasty. 10,11 The device named transoral gastroplasty (Satiety, Palo Alto, CA) contains a stapler body with two jaws and a septum with retraction wire to orient the stomach tissue for capture and stapling. Suction pulls tissue from the anterior and posterior walls of the stomach into the device and the stapler is closed and fired.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of intraluminal restrictive techniques for obesity are ongoing but durability of effect is in question. 10,11 Numerous mucosal ablation and excision methods for Barrett's esophagus have been devised; ablation techniques include photodynamic therapy, ultrasonic ablation, Argon beam coagulation, radiofrequency ablation, cryotherapy ablation, and bipolar electrocoagulation. [12][13][14][15] The primary excision technique is endoscopic mucosal resection (EMR) which is limited by cautery margins, specimen disorientation, and small size.…”
Section: Introductionmentioning
confidence: 99%
“…Moreno et al [20] reported more encouraging results in the second human pilot study due to those technical improvements of the procedure. Eleven patients (mean BMI 41.6 ± 4.3, range 37–53) were enrolled in this study.…”
Section: Restrictive Endoscopic Proceduresmentioning
confidence: 99%
“…La perte d'excès pondéral (PEP) était de 24,4 % à six mois chez des patients dont l'IMC moyen était de 43,3 avant la procédure [15]. Il est possible de modifier la poche après trois mois en cas de perte de poids insuffisante, en rajoutant des agrafes [16].…”
Section: Gastroplasties Endoscopiquesunclassified